Kadar TNF-Î± dan IL-1Î² cairan sulkus gingiva setelah pemasangan mahkota akrilik - Edy Machmud; Roswita Roswita (Journal of Dentomaxillofacial Science, 2007)
Cervical margin of fixed denture either jacket crown or bridge, is usually placedsubgingivally for the natural look, however this can sometimes cause gingivalinflammation. Moreover, if the restoration material is acrylic, it sometimes can irritateoral tissue. The aim of this study was to investigate the effect of acrylic, used as fixeddenture material, to gingival tissue reaction. This was an experimental study, using preand post test of 5 acrylic jacket crowns, made to patients in the ProsthodonticDepartment, Dental Hospital of Hasanuddin University. Gingival crevicular fluid (GCF)was collected before preparation, and three weeks after insertion of the jacket crowns,then pro-inflammatory cytokines; TNF-Î± and IL-1Î² were examined. The results analyzedby Wilcoxon sign rank test (p<0.05). The results showed the elevation of TNF-Î± and IL1Î²concentration after acrylic jacket crown insertion compare with the concentrationbefore preparation. The conclusion of this study is acrylic restoration material may causegingival inflammation.